Bahasa Indonesia sebagai Alat Pemersatu Bangsa - I Nyoman Temon Astawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Language is a national identity. The Indonesian nation has a unified language that is used by all its people to communicate. A great nation needs language as a unifying agent so that communication becomes easier and fosters a sense of nationalism in every area it covers. Indonesian is the language of unity that is upheld by all Indonesians. This is reflected in the third pledge of the 1928 Youth Pledge which reads,